(untitled) (Research, Society and Development, 2020)
In this paper, we look forward to understand what is the scope of scientific production about organizational studies on postmodernity. In order to achieve it, we perform a quantitative study (bibliometric), retrieving scientific articles indexed in the Web of Science base, in the period between 2000 and 2018. After applying several filters, we arrived at 432 works that were analyzed by the VOSviewer software. Among other points, we expose the oscillation of productions on the theme without a time interval, the main journals, the most cited authors and the suggestions for future studies raised by these papers. We concluded that organizational studies in postmodernity continue with a lot of attention from academia, since it was possible to detect a growth in the number of publications on the subject in this time frame, and, with this, we have assumed that this number tends to grow, encompassing more new themes, which indicates the possibility that the theme will be further explored in the future.